Innovation and leadership in the public sector : the Australian experience - Moussa, Mahmoud (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Using empirical data, this book uniquely presents the dynamics of innovation within public sector organisations and identifies the most crucial factors that promote innovation or the determinants that enhance innovation activities. It presents a macro and micro analysis of workplace innovation in the Australian public sector written by a combination of practitioners and academics to provide both theoretical and practical insights. The book reviews the relationship between culture and workplace innovation as a multi-dimensional, subjective and context specific phenomenon operating dynamically as organisational innovation, organisational climate for innovation, team and individual innovation. It identifies a variance in the perception of workplace innovation and organisational culture between public sector employees with different demographic and employment characteristics. The demographic and employment characteristics confirm that employees in a Public Sector Department of State exhibit significant differences between various groups in how culture impacts on workplace innovation. This knowledge assists practitioners in developing positive cultural environments that support the development of workplace innovation and raise awareness in considering the differences within organisations caused by an individual's characteristics. Lastly, the book reviews public organisations around the world and provides a cross cultural comparison of public sector innovation and leadership. This includes a review of the major forms of public sector systems in operation and how this relates to innovation and leadership. Innovation and Leadership in the Public Sector is written for academics and students interested in the public sector innovation field. It's suitable for both graduate and undergraduate students and researchers in the fields of public administration, management policy, organisational behaviour, human resources management (HRM), and human resources development (HRD) courses. Additionally, this book is suitable for middle-to senior level administrators or managers who wish to develop more innovative public sector organisations"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change -- Australia; Organizational behavior -- Australia; Leadership -- Australia; Public administration -- Technological innovations -- Australia; BUSINESS & ECONOMICS / Knowledge Capital; BUSINESS & ECONOMICS / Development / General; BUSINESS & ECONOMICS / Entrepreneurship